Optimization of Customer Complain Handling at Grapari East Java - Santoso, Larisa Elga Amalia; Rachmaningrum, Nilla; Muhsin, Muhsin (Journal of Informatics and Communication Technology (JICT), 2024)
The operational process at GraPARI is a benchmark for PT Telkomsel's success in the service sector which will later influence customer loyalty in using the product and ultimately increase revenue. Therefore, the potential of GraPARI services must be maximized, especially in terms of complaint handling. The high quality of service can be seen from the number of customers who come, the orderly and comfortable queue model, and the quick and precise solutions from customer service for all complaints lodged by customers. This research was conducted to create a system for monitoring the most effective traffic handling of customer complaints, thereby speeding up the complaint handling process using parameters of customer quantity, customer service productivity, and ending in the back office as a case executor. From these three parameters, cases are first categorized into three channels (human error, system error, and unique requests). The calculation results show that from all these categories, the process of handling them is slow with an Out Of SLA ratio of almost 80%. After a simulation of optimization using tandem channels, the estimated optimal duration decreased as the number of servers used increased, with the traffic is reduced by 7% by using 10 additional servers in the tandem channels